1968
DOI: 10.1901/jaba.1968.1-1
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF TEACHER ATTENTION ON STUDY BEHAVIOR1

Abstract: The effects of contingent teacher attention on study behavior were investigated. Individual rates of study were recorded for one first-grade and five third-grade pupils who had high rates of disruptive or dawdling behavior. A reinforcement period (in which teacher attention followed study behavior and non-study behaviors were ignored) resulted in sharply increased study rates. A brief reversal of the contingency (attention occurred only after periods of non-study behavior) again produced low rates of study. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
175
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(188 citation statements)
references
References 7 publications
13
175
0
Order By: Relevance
“…A number of recent studies have investigated the effects of contingent teacher attention on various student behaviors, i.e., attending, instruction following, verbal, and disruptive behavior in the public school classroom (Hall, Lund, Jackson, 1968;Hall, Panyan, Rabon, and Broden, 1968;Shutte and Hopkins, 1970;Thomas, Becker, and Armstrong, 1968 Baer (1970), used a consistent training procedure to modify teacher attending in preschool settings.…”
mentioning
confidence: 99%
“…A number of recent studies have investigated the effects of contingent teacher attention on various student behaviors, i.e., attending, instruction following, verbal, and disruptive behavior in the public school classroom (Hall, Lund, Jackson, 1968;Hall, Panyan, Rabon, and Broden, 1968;Shutte and Hopkins, 1970;Thomas, Becker, and Armstrong, 1968 Baer (1970), used a consistent training procedure to modify teacher attending in preschool settings.…”
mentioning
confidence: 99%
“…The findings emphasized the importance of designing specific contingencies for specific target behaviors. Behavioral contingencies did not have the positive effect on performance often implied, nor were performance contingencies alone able to maintain acceptable classroom behavior.A number of recent studies (Hall, Lund, and Jackson, 1968;Thomas, Becker, and Armstrong, 1968;Hamblin, Buckholdt, Ferritor, Kozloff, and Blackwell, 1971) have shown that teachers could be trained to increase appropriate behavior and decrease disruptive behavior through modifying contingencies of reinforcement in the classroom. These techniques have been used with…”
mentioning
confidence: 99%
“…A number of recent studies (Hall, Lund, and Jackson, 1968;Thomas, Becker, and Armstrong, 1968;Hamblin, Buckholdt, Ferritor, Kozloff, and Blackwell, 1971) have shown that teachers could be trained to increase appropriate behavior and decrease disruptive behavior through modifying contingencies of reinforcement in the classroom. These techniques have been used with 'An earlier version of this paper was presented to the American Educational Research Association, March, 1970, Minneapolis, Minnesota. …”
mentioning
confidence: 99%
“…Though proactive measures, such as positive reinforcement (Hall, Lund, & Jackson 1968), demand fading, and behavioral momentum, are critical components of many programs, analyses of compliance contingencies are incomplete without consideration of reactive measures. Students in the process of developing compliance will at least occasionally engage in noncompliance and related behaviors, and whether specifically programmed or not, something happens after those problematic behaviors.…”
mentioning
confidence: 99%